Purification of linearized template plasmid DNA decreases double-stranded RNA formation during IVT reaction - Martínez, Juan; Lampaya, Verónica; Larraga, Ana; Magallón, Héctor; Casabona, Diego (Frontiers in Molecular Biosciences, 2023)
After the COVID-19 pandemic, messenger RNA (mRNA) has revolutionized traditional vaccine manufacturing. With the increasing number of RNA-based therapeutics, valuable new scientific insights into these molecules have emerged. One fascinating area of study is the formation of doublestranded RNA (dsRNA) during in vitro transcription (IVT) which is considered a significant impurity, as it has been identified as a major trigger in the cellular immune response pathway. Therefore, there is a growing importance placed to develop and optimize purification processes for the removal of this by-product.2 This is a provisional file, not the final typeset article more emphasis on the purification of linearized plasmids and potentially saving, in some instances, a purification step for mRNA following IVT.